Bisulfite reductase of Desulfovibrio vulgaris: explanation for product formation. - Drake, H L (1977)
Bisulfite reductase, purified from Desulfovibrio vulgaris, was coupled with the pyruvate phosphoroclastic reaction. Moderate to low reducing conditions resulted in the formation of trithionate; however, when the concentration of reductant was high, a mixture of trithionate and thiosulfate was formed. Sulfide was also a detectable product, but only when the concentration of bisulfite was low. Flavodoxin mediated native coupling between bisulfite reductase and the phosphoroclastic reaction. A model for bisulfite reductase activity is proposed.